THE EFFECT OF COMPANY PERFORMANCE, CORPORATE GOVERNANCE AND EXECUTIVE CHARACTERISTICS ON EXECUTIVE COMPENSATION OF CONSUMER GOODS COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Elvina, Elvina Elvina (Jurnal KIAFE, 2021)
This study aims to determine the effect of corporate performance, corporate governance and executive characteristics on executive compensation in consumer goods companies listed on the Indonesian stock exchange. The company's performance variable is measured by using the net profit margin, Institutional Share Ownership and the financial overview section in the company's annual report. The method used in this paper is quantitative and the data is obtained from the annual reports of consumer goods companies listed on the Indonesia Stock Exchange in 2015-2019. 41 of 58 consumer goods companies were taken as samples through a sampling method with certain criteria. The analytical technique used in this research is multiple linear regression analysis. The results of this study indicate that the company's performance has a significant positive effect on executive compensation, institutional share ownership has a positive and insignificant effect on executive compensation and executive characteristics have a positive and insignificant effect on executive compensation. REFERENCES Abrokwah, S., Hanig, J., & Schaffer, M. (2018). Executive Compensation and Firm Risk: An Examination Accross Industries. Review of Accounting and Finance, 17(3), 359-382. Adam, S., Gupta, A., &Leeth , J. (2010). Maximising Compensation: Organisational Level and Industry Gender Compistion Effects. Gender in Management, 25(5), 366-385. Agoes, Sukrisno. (2011). Auditing (Pemeriksaan Akuntan) oleh Kantor Akuntan Publik. Edisi 4. Penerbit Salemba Empat. Anthony, Robert N, dan Vijay Govindarajan. 2012. Management Control System. Jakarta: SalembaEmpat. Ayura, Dies Pra. 2013. "Pengaruh Latar Belakang Pendidikan , Pendidikan Berkelanjutan, Komitmen Organisasi dan Pengalaman Kerja Terhadap Kinerja Aparat Pengawas Intern Pemerintah (APIP)". Skripsi. Fleming, A., &Chisrtian, L. S. (2012). Factor Analysis of Exexcutive Compensation Determinants: Survey Evidence From Executives and Non-Executive INvestors. Corporate Governance, 12(1), 116-41. Jalbert, T., Furumo, K., & Jalbert, M. (2011). Does Educational BAcrkground Affect CEO Compensation and Firm Performance? The Journal of Applied Business Research, 15-36. Kristanto, J. C. (2018). Kinerja Perusahaan Terhadap Kompensasi Eksekutif Pada Perusahaan Yang Terdaftar di Indeks LQ 45 PEriode 2012-2016. Jurnal Ilimiah Mahasiswa Universitas Surabaya, 7(1). Lewellen, Katharina. (2003). Financing Decisions When Managers Are Risk Averse. Journal of Financial Economics, Vol 82 (No. 3), hal 551-589. Mardiyanti, U., Devi, M. S., &Suherman. (2013). Pengaruh Kinerja Perusahaan, Corporate Governance, dan Shareholder Payout Terhadap Kompensasi Eksekutif. Jurnal Riset Manajemen Sains Indonesia (JRMSI), 4(2). Miles, C. P., & Miles, G. (2013). Corporate Social Responsibility and Executive Compensation : Exploring the LInk . Social Responsibiity Journal , 76-90. Priyatno, Duwi. 2012. Cara Kilat Belajar Analisis Data dengan SPSS 20. Yogyakarta: Andi Offset. Rahayu , O. O. (2016). Pengaruh Kompensasi Eksekutif, Keterwakilan CFO Wanita, dan Karakteristik Eksekutif Terhadap Tindakan Pajak Agresif (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2014).Universitas Islam Negeri Syarif Hidayatullah, Jakarta, Indonesia Rampling, P., Eddie, I., & Liu, J. (2013). Executive Remuneration in China: a Literature Review. Asian Review of Accounting, 21(2), 128-143. Sari, S. P., &Harto, P. (2014). Kompensasi Esekutif dan Kinerja Operasional Perbankan Indonesia . Dipenogoro Journal of Accounting , 1-7. Scott, W. (2012). Fianancial Accounting Theory (6 ed.). Toronto: Pearson Education Canada. Suherman, Pardede, Y. Y., &Maridyanti, U. (2016). PengaruhKinerjaPerusahaan, Corporate Governance, dan Karakteristik Eksekutif Terhadap Kompensasi Eksekutif. Jurnal Keuangan dan Perbankan, 20(1), 1-9. Srimindarti, Ceacilia. (2004). Balanced Scorecard Sebagai Alternatif untuk MengukurKinerja. FokusEkonomi. 20(1) Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif dan R & D. Bandung: Afabeta. Tjahjono,K,H,(Ed).(2017).Manajemen Sumber Daya Manusia & Perilaku Organisasional. Yoygyakarta: Program Pasca sarjana Universitas Muhammadiyah Yogyakarta. Tunggal, W. A, (2012), Audit kecurangan dan akuntansiforensik, Harvarindo, Jakarta. https://www.idx.co.id/